1990
DOI: 10.1136/bjo.74.11.643
|View full text |Cite
|
Sign up to set email alerts
|

Fluorosilicone oil in the treatment of retinal detachment.

Abstract: We evaluated the use of a heavier-than-water fluorinated silicone oil in the treatment of 30 selected cases of complicated retinal detachment from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…The present data confirm other observa tions on the absence of toxicity of this com pound on the retina [7][8][9]11 ], as well as simi lar observations of lack of toxicity on the cor neal endothelium [4], The latter observation is of importance because comparisons of other toxic compounds on both corneal endo thelium and blood-retinal barrier have indi cated that the corneal endothelium is the more sensitive paradigm for toxicity evalua tion of such materials [4,[17][18][19][20] vitreous at a substantial volume (25% of the total capacity of the vitreous cavity), offers no overt toxic effects on the blood-retinal bar rier, albeit the rabbit retinal vasculature is not the same as that of a human eye. Prior studies on retinal toxicity of perfluoro-n-octane indi cated that even large quantities of this liquid (80-90% replacement of vitreous volume) caused no change in the electroretinogram, although some histopathological changes were indicated where the liquid contacted the retina [11],…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present data confirm other observa tions on the absence of toxicity of this com pound on the retina [7][8][9]11 ], as well as simi lar observations of lack of toxicity on the cor neal endothelium [4], The latter observation is of importance because comparisons of other toxic compounds on both corneal endo thelium and blood-retinal barrier have indi cated that the corneal endothelium is the more sensitive paradigm for toxicity evalua tion of such materials [4,[17][18][19][20] vitreous at a substantial volume (25% of the total capacity of the vitreous cavity), offers no overt toxic effects on the blood-retinal bar rier, albeit the rabbit retinal vasculature is not the same as that of a human eye. Prior studies on retinal toxicity of perfluoro-n-octane indi cated that even large quantities of this liquid (80-90% replacement of vitreous volume) caused no change in the electroretinogram, although some histopathological changes were indicated where the liquid contacted the retina [11],…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies with perfluoro-n-octane in the rabbit anterior chamber revealed that no toxicity occurred to the corneal endothelium following the re placement of about one quarter of the ante-rior volume with the liquid [4], On the other hand, another report on complete replace ment of the aqueous humor with fluid [5] indicated that corneal swelling without a change in corneal clarity occurred within the first 24 h of exposure. Some perfluorocarbon derivatives have been shown, however, to cause retinal toxicity [6] although fluorosilicone oil has been reported not to induce reti nal toxicity [7][8][9], as has perfluorophenanthrene [10]. Perfluoro-n-octane has also been reported to have great ocular tolerance for up to 6 months in rabbit eyes as judged by electroretinography.…”
Section: Introductionmentioning
confidence: 99%
“…So far no randomized clinical trial on the efficacy of heavier than water endotamponades exists for retinal detachments with inferior tears and inferior PVR. The success rate is lying between 50% (FsiO/silicone oil mixture [19]), 77% (fluorosilicone oil [21]), 78% (F 6 H 8 [7]), 86% (F 6 H 8 [22]) and 100% (perfluoroperhydrophenanthrene [23]). This wide discrepancy is mainly due to the fact that many authors assume as end-point criteria partial retinal reattachment, including eyes with endotamponade still filling the vitreous chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, florosilicone oil (FSiO; heavier than water) has been proposed as extended internal tamponade [10][11][12]. The FSiO bubble creates a free space located in the upper part of the vitreous chamber and delimited by the silicone bubble itself and the superior retina.…”
Section: Introductionmentioning
confidence: 99%